2012
DOI: 10.1002/aenm.201200184
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Polymer Solar Cells with Reduced Interface Recombination

Abstract: Interface recombination induced by the defect states in zinc‐oxide‐nanoparticle‐based electron extraction layer is reported as a significant loss‐mechanism of photocurrent collection. By choosing appropriate UV–ozone treatment conditions on the zinc oxide layer, inverted polymer solar cells show reduced interface recombination and thus improved power conversion efficiencies of up to 8.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(215 citation statements)
references
References 35 publications
3
212
0
Order By: Relevance
“…[14,[47][48] As reported by So and co-workers, UV-ozone treatment not only passivates the surface defects but also generates excess oxygen at the ZnO surfaces which may oxidize the polymers with higher-lying HOMO energies, such as P3HT, and hence degrade the device performance. [14] Upon successful attempts of EDT passivation on ZnO nanocrystal films, we further extended the EDT passivation approach to the ZnO films deposited from Sol-gel precursors. Inverted organic solar cells based on Sol-gel derived and EDT treated ZnO films were fabricated using either the P3HT: PC61BM blends or TQ1: PC71BM blends as active layers.…”
Section: Tq1:pc71bm Devices Using E-zno Interlayers and Solar Cells Bmentioning
confidence: 98%
See 3 more Smart Citations
“…[14,[47][48] As reported by So and co-workers, UV-ozone treatment not only passivates the surface defects but also generates excess oxygen at the ZnO surfaces which may oxidize the polymers with higher-lying HOMO energies, such as P3HT, and hence degrade the device performance. [14] Upon successful attempts of EDT passivation on ZnO nanocrystal films, we further extended the EDT passivation approach to the ZnO films deposited from Sol-gel precursors. Inverted organic solar cells based on Sol-gel derived and EDT treated ZnO films were fabricated using either the P3HT: PC61BM blends or TQ1: PC71BM blends as active layers.…”
Section: Tq1:pc71bm Devices Using E-zno Interlayers and Solar Cells Bmentioning
confidence: 98%
“…As shown in Figure 4b, the PL spectrum (excitation: 310 nm) of the P-ZnO film exhibits a narrow emission peak at ~366 nm corresponding to the band-edge emission and a board peak of visible emission centered at ~545 nm, which is attributed to the defect-related emission. [14,38] After EDT treatment, both the visible emission and the band-edge emission are almost completely quenched. We note that a similar PL quenching phenomenon was observed for the dodecanethiol modified ZnO nanocrystal films.…”
Section: Electronic and Molecule Model Of Edt Passivated Zno Nanocrysmentioning
confidence: 99%
See 2 more Smart Citations
“…Provided that the Voc did not change except for exposure times larger than 20 min, as seen in Figure 2E, we concluded that the 20 min UVN treatment led to the largest PCE as seen in Table S1. Such optimal performance was attributed to enhanced conductivity of the ZnO ETL and reduced interface recombination 29,34 , which was confirmed by the I-V 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 conductivity measurements from diode devices of ITO/ZnO (w/o UVN treatment) (100 nm)/Al, as shown in Figure S2. The electrical conductivity under illumination for UVNtreated ZnO film was ~ 4.16×10 -4 S/m, about 1.5 times higher than the one from as-prepared ZnO film.…”
Section: Influence Of Uvn Treatment On Device Performancementioning
confidence: 99%